FLOT versus FLOT/Trastuzumab/Pertuzumab perioperative therapy of human epidermal growth factor receptor 2-positive resectable esophagogastric adenocarcinoma: a randomized phase II trial of the AIO EGA study group - Hofheinz, Ralf-Dieter; Merx, Kirsten; Haag, Georg Martin; Springfeld, Christoph; Ettrich, Thomas; Borchert, Kersten; Kretzschmar, Albrecht; Teschendorf, Christian; Siegler, Gabriele; Ebert, Matthias; Goekkurt, Eray; Mahlberg, Rolf; et al. (Journal of clinical oncology, 2022)
High pathologic complete response (pCR) rates and comparably good survival data were seen in a phase II trial combining perioperative fluorouracil, leucovorin, oxaliplatin, and docetaxel (FLOT) chemotherapy with trastuzumab for resectable, esophagogastric adenocarcinoma (EGA). The current trial evaluates the addition of trastuzumab and pertuzumab to FLOT as perioperative treatment for human epidermal growth factor receptor 2-positive resectable EGA.